Organic and Inorganic Fertilizers Effect to Mustard Plants (Brassica juncea L.) Growth - Layliyah; Luqman Al-Farisi, Bayuda (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2024)
This research aims to investigate the effects of organic and inorganic fertilizers on the growth of Mustard plants (Brassica juncea L.). The research was conducted at the BPP Rubaru office, Sumenep. The experimental method used a Randomized Block Design (RBD) with two treatments: organic fertilizer (liquid cow manure) and inorganic fertilizer (NPK), each replicated three times. Observed parameters included plant height and leaf width. The research results showed that the use of organic fertilizer had a faster growth effect on plant height and leaf width compared to inorganic fertilizer (NPK), and was able to contribute to the quality of leaf structure compared to inorganic fertilizer (NPK). Overall, the suggestion to combine the use of organic and inorganic fertilizers could be an interesting alternative to carry out in further research.